Cottontails : little rabbits of field and forest - Fisher, Ronald M. (Washington, D.C. : National Geographic, 1989)
Illustrates how the cottontail rabbit explores its environment, eats, washes, senses danger, rests, and cares for its young. Also describes wild and domestic rabbits around the world.
Bibliography: p. [34].
2.5
K-3
Keywords: Cottontails -- Juvenile literature; Cottontails; Rabbits; Cottontails; Rabbits